Cross‐Sectional Association Between Number of Teeth and High‐Sensitivity C‐Reactive Protein Among Middle‐Aged Germans. Issue 3 (1st March 2016) - Oluwagbemigun, Kolade; Bergmann, Manuela; Pischon, Nicole; Dietrich, Thomas; Boeing, Heiner
Abstract : Background: The association between number of teeth and low‐grade systemic inflammation deserves consideration within the European Prospective Investigation into Cancer and Nutrition (EPIC)‐Potsdam since the association between number of teeth and myocardial infarction has been established. Methods: Two subsamples (n = 2, 439 and 728) were randomly selected from EPIC‐Potsdam. Participants provided information on number of natural teeth, anthropometry, lifestyle factors, and illness‐related factors. High‐sensitivity C‐reactive protein (hsCRP) was measured from serum. Adjusted means of hsCRP across five categories of numbers of teeth in each subsample and in the combined sample were determined, and linear trends were checked. Non‐linear associations were investigated with restricted cubic spline (RCS) regression. Results: In the first subsample, the full multivariable‐adjusted model showed that participants with 28 to 32, 24 to 27, 18 to 23, 1 to 17, and 0 teeth had mean hsCRP values of 1.32, 1.39, 1.54, 1.38, and 1.48 mg/L, respectively; in the second subsample, mean hsCRP values were 1.64, 1.67, 1.73, 1.47, and 1.87 mg/L; combined hsCRP values were 1.49, 1.53, 1.64, 1.44, and 1.65 mg/L. No linear trend was observed in these models, and RCS regression showed no non‐linear association. Conclusion: This study shows that number of teeth has a weak association with hsCRP, if any, thereby excluding this marker of low‐grade systemic inflammation as a possible explanation for the association between number of teeth and myocardial infarction.